Early data from the first population-wide breast cancer-specific registry in Hong Kong. - Cheung, P; Hung, W; Cheung, C; Chan, A; Wong, T; Li, L; Chan, S; Chan, K; Choi, P; Kwan, W; Yau, C; Chan, E; et al. (2012)
BACKGROUND: Current measures for breast cancer prevention and options for treatment adopted in Hong Kong are mainly based on research data and clinical evidence from overseas. It is essential to establish a cancer-specific registry to monitor the status of breast cancer in Hong Kong. OBJECTIVES: We summarized the current status of breast cancer in Hong Kong based on the data collected from Hong Kong Breast Cancer Registry (HKBCR). METHODS: Prevalent and newly diagnosed breast cancers (including in situ and invasive breast cancers) were registered in the HKBCR. Information on patient demographics, risk factors, medical information, and survival were analyzed and reported in this study. RESULTS: Data of 2,330 breast cancer patients were analyzed. We observed an earlier median age at diagnosis in Hong Kong than those reported in other countries. Distribution of cancer stage was: stage 0 (11.4%), stage I (31.4%), stage II (41%), stage III (12.5%), stage IV (0.8%), and unclassified (2.9%). The percentages of patients who received surgery, chemotherapy, radiation therapy, and endocrine therapy were 98.7, 67.9, 64.8, and 64.1%, respectively. At a median follow-up of 1.2 years, locoregional recurrence was recorded at 2%, distant recurrence at 2.8%, and breast-cancer-related mortality at 0.3%. CONCLUSIONS: The HKBCR serves as a surveillance program to monitor disease and treatment patterns. It is pivotal to support research for more effective breast cancer prevention and treatment strategies in Hong Kong.